Strategies of Targeting Inflammasome in the Treatment of Systemic Lupus Erythematosus - Liu, Yaling; Tao, Xinyu; Tao, Jinhui (Frontiers in Immunology, 2022)
Systemic Lupus Erythematosus (SLE) is an autoimmune disease characterized by multiple organ dysfunction resulting from the production of multiple autoantibodies and adaptive immune system abnormalities involving T and B lymphocytes. In recent years inflammasomes have been recognized as an important component of innate immunity and have attracted increasing attention in their pathogenic role in SLE. In short, inflammasomes regulate the abnormal differentiation of immune cells, modulate pathogenic autoantibodies, and participate in organ damage. However, due to the clinical heterogeneity of SLE, the pathogenic roles of inflammasomes are variable, and thus the efficacy of inflammasome-targeting therapies is uncertain. To provide a foundation for the development of such therapeutic strategies, in this paper we review the role of different inflammasomes in the pathogenesis of SLE and their correlation with clinical phenotypes and propose some corresponding treatment strategies.